Makna Perjamuan Malam Kudus Bagi Umat Kristen Lukas 22:19-20 Sebuah Respon Atas Tuduhan Bahwa Orang Kristen Adalah Kanibal - Melda Greace; Malik Bambangan (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
the liberation of the Israelites from slavery in Egypt, marking God's intervention in the history of His people and the beginning of a new grain harvest. On the other hand, Easter marks the resurrection of Jesus Christ, a symbol of victory over sin and death, and the culmination of salvation provided through His sacrifice on the cross. In this context, the Eucharist becomes an important sacrament symbolizing the body and Passover and Easter have deep meanings in their respective religious traditions. Passover (Pesach) celebrates blood of Christ. The bread, as a symbol of His broken body, and the cup, as a symbol of His shed blood, remind Christians of God's infinite sacrifice and love. However, in the early days of Christianity, the practice of the Eucharist was often misunderstood, leading to accusations of cannibalism against Christians. This misunderstanding arose because the terms "body" and "blood" were interpreted literally by outsiders. To counter these accusations, Christian apologists, such as Justin Martyr and Tertullian, attempted to provide a theological explanation for the symbolism, emphasizing that the Eucharist was a spiritual and not a physical act. Thus, both Easter and the Eucharist reflect the profound themes of liberation and hope, as well as the importance of a correct understanding of the symbolism of Christian teaching to avoid harmful misunderstandings. This shows that a proper understanding of religious traditions can strengthen faith and strengthen relationships among believers.